2020
DOI: 10.1364/oe.392536
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure-modulated planar high spectral resolution spectro-polarimeter

Abstract: We present a planar spectro-polarimeter based on Fabry-Pérot cavities with embedded polarization-sensitive high-index nanostructures. A 7 µm-thick spectro-polarimetric system for 3 spectral bands and 2 linear polarization states is experimentally demonstrated. Furthermore, an optimal design is theoretically proposed, estimating that a system with a bandwidth of 127 nm and a spectral resolution of 1 nm is able to reconstruct the first three Stokes parameters with a signal-to-noise ratio of -13.14 dB with respec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The sensor concept we will employ has been introduced in [20,21,22]. It consists of a multilayer structure that can perform both polarization and spectral filtering and can be integrated on top of a CMOS/CCD sensor.…”
Section: Sensor Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor concept we will employ has been introduced in [20,21,22]. It consists of a multilayer structure that can perform both polarization and spectral filtering and can be integrated on top of a CMOS/CCD sensor.…”
Section: Sensor Conceptmentioning
confidence: 99%
“…Since circular polarization in atmospheric remote sensing from space is orders of magnitude smaller than linear polarization and to our knowledge not strictly required for aerosol sensing, the waveplate concept has not been further investigated. Experimental results of single cavity filters manufactured in the SWIR can be found in [20], where a single cavity DBR with metasurface was created and tested by making use of aSi:H pillars (amorphous hydrogenated silicon). While the materials used for those investigations are different than the ones proposed here, those measurements act as proof of principle for the presented concept.…”
Section: Sensor Conceptmentioning
confidence: 99%
“…Recent research has shown that by introducing metasurfaces into the FP cavity, such as high refractive index nanostructure arrays, the effective refractive index can be adjusted [28][29][30][31]. The incorporation of high refractive index nanostructures increases the phase shift of the cavity and the corresponding red shift of the resonance peak [32] so that the central wavelength can be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…The working principle of these cameras is similar to a conventional RGB camera. In the case of RGB cameras, the color information is generated using spectral filters on the camera sensor arranged in a 2-by-2 Bayer matrix, from which a full scale color image is reconstructed [10,11]. This approach is enhanced for hyperspectral imaging by increasing the size of the filter matrix, e.g.…”
Section: Introductionmentioning
confidence: 99%